12mn+4m+8mn+6m=

Simple and best practice solution for 12mn+4m+8mn+6m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12mn+4m+8mn+6m= equation:


Simplifying
12mn + 4m + 8mn + 6m = 0

Reorder the terms:
4m + 6m + 12mn + 8mn = 0

Combine like terms: 4m + 6m = 10m
10m + 12mn + 8mn = 0

Combine like terms: 12mn + 8mn = 20mn
10m + 20mn = 0

Solving
10m + 20mn = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '10m'.
10m(1 + 2n) = 0

Ignore the factor 10.

Subproblem 1

Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0

Subproblem 2

Set the factor '(1 + 2n)' equal to zero and attempt to solve: Simplifying 1 + 2n = 0 Solving 1 + 2n = 0 Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2n = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2n = 0 + -1 2n = 0 + -1 Combine like terms: 0 + -1 = -1 2n = -1 Add '-2n' to each side of the equation. 2n + -2n = -1 + -2n Combine like terms: 2n + -2n = 0 0 = -1 + -2n Simplifying 0 = -1 + -2n The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

m = {0}

See similar equations:

| (n-2)180= | | 2v^2+v+64=0 | | -4-4x+2x=-10 | | 1+4x=-31 | | a+-0.4=-3 | | 6(1+3d)=-8(-2m+5)-4 | | -3(4t-2)+7t=4t-4 | | 6x-27=4x+12 | | cx+5=dx-3 | | 5+2(x+1)=2n | | 9y+13=30 | | w^2-11=2-5w^2 | | 6x+40=8x-20 | | 5*x+2=11-x*8 | | 4b-8=1+6-3b-1 | | 2x^2+kx^2-2kx-16=0 | | 2x-(x+2)=2x-0.1 | | 6=7x-x+6 | | w*w+9=6w | | 4x+172=180 | | .3T-2.1C-2.3=7.6 | | 5r+4=9(r-3) | | (m/2)-(1/m)=(6m+5/12) | | X^2+6X=34 | | 15x-75=90 | | Y=(15x+10)(15x-2) | | 3(2a-b)-5a= | | 7v+2=0 | | 2x-4x+4=x-3+7 | | 7=3(t-5)-t | | 3x^2-2x-8=448 | | Y=225x^2+120x+20 |

Equations solver categories